2016
DOI: 10.9790/3013-06715163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Process Variables and Formulation Excipients on the Engineering of Sertaconazole Solid Lipid Nanoparticles

Abstract: Abstract:The present research work focuses on the study of influence of various ingredients, concentration of ingredients and process parameters on the formulation of Solid lipid nanoparticles (SLN). The sertaconazole loaded solid lipid nanoparticles (SERT-SLN) were prepared by simple, easily reproducible and novel modified solvent emulsification method. Lipid and surfactant solubilizing potential was determined by solubility study. To improve the properties of SLN some excipients were added like cosurfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The addition of GMS could decrease the particle size as it has self-emulsifying property due to its structure which has a saturated carbon chain length. This structure enables it to capture more drugs and have a uniform particle size in the nanosize range [48]. These findings were agreed with Gardouh et al, [49], who found that lipid hydrophilicity and self-emulsifying properties affected by the lipid crystal's appearance (and hence the surface area) had an indirect effect on the final size of NLC dispersions.…”
Section: Particle Size Analysissupporting
confidence: 87%
“…The addition of GMS could decrease the particle size as it has self-emulsifying property due to its structure which has a saturated carbon chain length. This structure enables it to capture more drugs and have a uniform particle size in the nanosize range [48]. These findings were agreed with Gardouh et al, [49], who found that lipid hydrophilicity and self-emulsifying properties affected by the lipid crystal's appearance (and hence the surface area) had an indirect effect on the final size of NLC dispersions.…”
Section: Particle Size Analysissupporting
confidence: 87%
“…Studies on lipid-based nanoparticles have shown that several factors such as surfactant type and its concentration, instrumental conditions, and lipids used in their formulations can have impact on PDI and particle size. 132 A study on encapsulation of vitamin E in nanoliposome revealed that the formulation of liposomes by hydrophobic stabilizers such as gamma oryzanol and lauric acid leads to an increase in the particle size. Though, hydrophilic stabilizer such as PEG 400 did not have significant effect on mean size.…”
Section: Important Properties Of Vitamin-loaded Nanoliposomes 51 Particle Size Pdi and Zeta Potential Of Nanoliposomesmentioning
confidence: 99%
“…Studies on lipid-based nanoparticles have shown that several factors such as surfactant type and its concentration, instrumental conditions, and lipids used in their formulations can have impact on PDI and particle size. 147 …”
Section: Important Properties Of Vitamin-loaded Nanoliposomesmentioning
confidence: 99%